REPRODUKSI KULTURAL DAN HABITUASI PADA WISATAWAN KAMPUNG MILIADER DESA TLOBO, KECAMATAN JATIYOSO, KABUPATEN KARANGANYAR - B.Mayang Sada Wibowo; Shubuha Pilar Naredia (Jurnal Analisa Sosiologi, 2024)
The term Billionaire Village appeared in Tlobo Village because of the existence of luxury housing after the construction of the Jlantah Dam. The identity of the Billionaire Village is embedded by the surrounding community. There are new forms of cultural reproduction and activities (habituation) due to the existence of these identities. The purpose of the study is to analyze cultural reproduction and habituation in tourists in the Billionaire Village of Tlobo Village using a scheme of cultural reproduction practices. This study uses a single case study approach. The data is sourced from information obtained directly through interviews, while other supporting data is obtained through literature studies on supporting literature. Data collection techniques are carried out by observation, in-depth interviews, and documentation. Interactive models are used in data analysis. The validity of the data is carried out to ensure the validity of the data. The results of the study found that there was a cultural reproduction practice that occurred in the Tlobo Village Billionaire Village carried out by tourists. These actors have a habitus that is accumulated with various capital. The practice of cultural reproduction occurs as a result of the struggle for positions carried out by actors with the accumulation of habitus and capital. The forms of cultural reproduction found are; changes in content production activities and tourism activities. In the Tlobo Village Billionaire Village, habituation is divided into, namely; socio-cultural habituation and socio-economic habituation. One of the habituations is realized by the many shops and food stalls because of the community's meaning of tourist areas. Habituation appears as an impact/form of cultural reproduction practices that occur on the knowledge structure of each actor in the identity arena of the Tlobo Village Billionaire Village.